Structural, mechanical, electronic and optical properties of N-decorated single-walled silicon carbide nanotube photocatalyst for hydrogen evolution via water splitting: a DFT study - Yahaya Saadu Itas; Razif Razali; Salisu Tata; Mohammed Kolo; Hamid Osman; Abubakr M. Idris; Mayeen Uddin Khandaker (Science and Technology of Advanced Materials, 2023)
ABSTRACTThis work investigates the fundamental photocatalytic properties of nitrogen-doped single-walled silicon carbide nanotubes (N-doped SWSiCNTs) for hydrogen evolution for the first time. Investigations of the structural, mechanical, electronic, and optical properties of the studied systems were carried out using popular density functional theory implemented in quantum ESPRESSO and Yambo codes. Analysis of the structural properties revealed high mechanical stability with the 3.6% and 7.4% N-doped SWSiCNT. The calculated band gap of the N-doped SWSiCNT with 3.6% demonstrated a value of 2.56 eV which is within the photocatalytic range of 2.3 eV−2.8 eV. The hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) potentials of the 3.6% N-doped SWSiCNT also showed good agreement with previous theoretical data. The studied material showed the best photocatalytic performance in both parallel and perpendicular directions by absorbing photons in the visible region. Therefore, the observed structural, mechanical, electronic and optical behaviors demonstrated by the 3.6% N-doped SWSiCNT exposed it as a better photocatalyst for hydrogen production under visible light.